Functional Outcome Analysis After Anterolateral Thigh Flap Reconstruction of Pharyngoesophageal Defect. Issue 2 (August 2015) - Huang, Tsung-Chun; Hsu, Yung-Chang; Chen, Hung-Chi; Chang, Sophia Chia-Ning; Chen, Hsin-Han
Abstract : Background: Pharyngoesophageal defects are traditionally reconstructed with jejunal or radial forearm flaps. Recently, anterolateral thigh flaps have served for pharyngoesophageal reconstruction. We tell of our experience with anterolateral thigh flap for the reconstruction of pharyngoesophageal defect for the past 5 years. This study presents another modified flap design and refinement of surgical techniques. Methods: In all, 45 pharyngoesophageal reconstructions were performed during 2006 to 2011, namely patch (n = 18), near-circumferential (n = 8), and circumferential defect (n = 19) reconstructed by 2 plastic surgeons with the same trapezoid anterolateral thigh flap design. Results: Total flap loss occurred in 2 patients (4%). Two patients experienced partial flap necrosis. Fistulas occurred in 8 patients, but only 5 of these needed further suture ligation or local flap treatment. Postoperative strictures without tumor recurrence were identified in 4 patients (9%). Forty patients (88.9%) could tolerate oral diet; 34 of these ate soft or solid food. Conclusions: Anterolateral thigh flap offers good coverage and swallowing function in the reconstruction of hypopharyngeal defect. Trapezoid drawing of anterolateral thigh flap makes the design simplified, with an accepted complication rate.